Research progress on the application of Lacticaseibacillus rhamnosus GG in pediatric respiratory diseases - Liu, Yang; Chen, Yan; Liao, Huijuan; Sun, Shijie; Zhang, Xiaohu; Xie, Liang; Liu, Hanmin (Frontiers in Nutrition, 2025)
Respiratory diseases are a leading cause of morbidity in children globally, with significant healthcare costs. The overuse of conventional treatments like antibiotics has raised concerns about antibiotic resistance and side effects. Lacticaseibacillus rhamnosus GG (LGG), one of the most extensively studied probiotics, has gained attention as a potential adjunct therapies due to their ability to modulate the gut microbiota and immune responses. This review aims to assess the effectiveness of LGG in managing pediatric respiratory diseases, including respiratory tract infections (RTI), cystic fibrosis (CF), and asthma. Clinical trials suggest LGG can reduce the incidence and severity of RTI, improving CF symptoms, and enhancing quality of life in children. However, evidence for its benefits in asthma remains inconclusive. Its mechanisms include modulating immune responses, enhancing gut barrier function, and maintaining a microbial homeostasis via the gut-lung axis. Existing studies are often limited by small sample sizes, heterogeneity in intervention protocols, and short follow-up periods. Emerging technologies and novel formulations, hold promise for unraveling the complex interactions among LGG, the gut-lung axis, and respiratory health. These advancements could pave the way for personalized probiotic therapies, highlighting the potential of LGG as a cost-effective, adjunctive therapy for pediatric respiratory diseases. This review underscores the broader significance of integrating LGG into pediatric healthcare, while calling for future research to overcome current limitations, optimize clinical protocols, and explore innovative therapeutic strategies.